S27 Sustained anti-inflammatory effects of lumacaftor-Ivacaftor in sputum and peripheral blood samples of adult cystic fibrosis patients- an observational study. (11th November 2022) - Arooj, P; Morrissy, D; Ronan, N; McCarthy, Y; Fleming, C; Eustace, JA; Murphy, DM; Plant, BJ
Abstract : Introduction: Previous studies showed that the combination of CFTR corrector and potentiator, lumacaftor-ivacaftor (LUMA-IVA) provides meaningful clinical benefits in patients with cystic fibrosis (PWCF) who are homozygous for the Phe508del CFTR mutation. However, little is known about the effect of LUMA-IVA on proinflammatory cytokines (PICs). We sought to investigate the impact of lumacaftor-ivacaftor CFTR modulation on circulatory and airway cytokines before and after 12 months of lumacaftor-ivacaftor treatment in a real world setting. Methods: In this study, we assessed both plasma and sputum proinflammatory cytokines, as well as standard clinical outcomes including FEV1%, BMI, sweat chloride and pulmonary exacerbations at baseline and prospectively for one-year post commencement of LUMA-IVA in forty -four patients with CF aged sixteen years and older with homozygous for the Phe508del CFTR mutation. Results: Significant reduction in plasma IL-8 (p<0.001), TNF-α (p<0.001), IL-1ß (p<0.001) levels and in sputum IL-6 (p<0.05), IL-8 (p<0.01) and TNF-α (p<0.001) levels were observed after lumacaftor -ivacaftor therapy. Clinically significant improvements in FEV1% predicted (mean +3.38%, p=0.002), BMI (mean +0.8 kg/m2, p<0.001), sweat chloride (mean -19 mmol/l, p<0.001), as well as in intravenous antibiotics usage (mean -0.70, p<0.001) and hospitalization (mean-0.38, p=0.002) were observed after initiation of lumacaftor-ivacaftor therapy. Conclusions: This real -world study demonstrates that lumacaftor-ivacaftor has significant and sustained beneficial effects on both circulatory and airway inflammation. Our findings show that lumacaftor-ivacaftor results in anti-inflammatory changes in addition to its ability to stimulate CFTR function, which could contribute to improve standard clinical outcomes.